PHOTOVOLTAIC EFFECT AT SPIN RESONANCE IN QUANTUM MAGNETIC FIELD - N. N. Chernyshov; A. V. Belousov; M. A. F. Alkhawaldeh; V. M. Pisarenko; I. V. Rogozin (Радиофизика и электроника, 2019)
Subject and purpose. The article is devoted to the investigation of the photovoltaic effect in n-InSb under optical transitions between the spin subbands of the Landau levels for the ultraquantum limit. The geometry is considered when the polarization is perpendicular, and the current is directed along the magnetic field. The effect is due to the cubic terms in the Hamiltonian that exist due to the absence of an inversion center. The dependence of the current on the magnetic field has a resonance character. Such an effect is associated with resonance in the intermediate state and interference of the second-order transition amplitudes with respect to relativistic contributions to the Hamiltonian. The aim of the work is a theoretical and experimental study of the photovoltaic effect for spin resonance. Methods and methodology. The photovoltaic effect in optical transitions between the spin-subzones of the Landau le-vels is considered in the article. The geometry of the system under investigation is as follows: the polarization of the electric field is perpendicular, and the current is directed along the lines of force of the magnetic field. Calculation of the magnetic field components and current density was carried out using the finite element method, which is implemented in the ANSYS software. The dependence of the current density on the magnetic field strength is analyzed. This dependence has a resonance character and contains field contributions with even and odd numbers. This effect is associated with resonance in the intermediate state and interference of the amplitudes of relativistic second-order contributions to the Hamiltonian. Results. The practical value and scientific novelty lie in the study of the photovoltaic effect at spin resonance. Since a weakly absorbing medium is considered, an increase in the photovoltaic effect is observed as a result of the divergence of the mean square electric field modulus. The practical significance of the results lies in the development of a methodology for studying band parameters, and the terms in the Hamiltonian can lead to electrodipole transitions and photocurrents. Conclusions. The results of the photovoltaic effect study supplement the experimental measurements of light absorption in a weakly absorbing medium. The same components in the Hamiltonian can lead to electric dipole transitions.